Uji Efektivitas Ekstrak Daun Cemba (Senegalia rugata) terhadap Penyembuhan Luka Sayat pada Kelinci (Oryctogalus cuniculus): Testing the Effectiveness of Cemba (Senegalia rugata) Leaves Extract on Cure Incision Wounds Healing in Rabbits (Oryctolagus cuniculus) - Dewi Rahmadina; Novita Eka Putri Kartab; Niken Indriyanti (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2023)
Wound medicine is a pharmaceutical preparation that helps speed up wound healing. Wound medications such as povidone-iodine contain antiseptics to prevent infection. Povidone iodine has bactericidal activity, low toxicity, and affordable price. However, in some cases, povidone-iodine can cause allergies. Cemba leaves (Senegalia rugate) are an endemic plant empirically used to heal open wounds. This study aims to determine the yield of cemba leaf extract, the ability of cemba leaf extract to heal cuts, and the concentration of cemba leaf extract, which can provide the best activity as a wound healer. This test uses rabbits as subjects which will be given treatment in the form of a control test of cemba leaf extract with an ointment base concentration variant of 5%, 10%, and 15%; for the comparison control, a negative control is used in the form of the base, positive control in the form of betadine ointment, and standard control. Based on the research that has been done, it was found that the yield of cemba leaf extract was 31.82%. The results of the phytochemical screening showed that cemba leaf extract contained secondary metabolites in the form of alkaloids, flavonoids, tannins, steroids, and saponins. The test results showed that a 5% cemba leaf extract and positive control concentration could heal wounds on the 10th day. Keywords: Cemba leaf, Povidone iodine, Cut wound healing, Phytochemical screening Abstrak Obat luka adalah sediaan farmasi yang membantu mempercepat proses penyembuhan luka. Obat luka seperti povidone iodine mengandung antiseptik untuk mencegah infeksi. Povidone iodine memiliki aktivitas bakterisidal, toksisitasnya rendah, dan harganya terjangkau. Akan tetapi pada beberapa kasus, povidone iodine dapat menimbukan alergi. Daun cemba (Senegalia rugata) adalah tanaman endemik yang secara empiris dimanfaatkan sebagai penyembuh luka terbuka. Penelitian ini bertujuan untuk mengetahui hasil rendemen dari ekstraksi daun cemba, kemampuan ekstrak daun cemba sebagai penyembuh luka sayat, konsentrasi ekstrak daun cemba yang dapat memberikan aktivitas paling baik sebagai penyembuh luka sayat. Pengujian ini menggunakan kelinci sebagai subjek yang akan diberikan perlakuan berupa kontrol uji ekstrak daun cemba dengan varian konsentrasi basis salep yaitu 5%, 10%, dan 15%, untuk kontrol pembanding digunakan kontrol negatif berupa basis, kontrol positif berupa salep betadine, dan kontrol normal. Berdasarkan penelitian yang telah dilakukan, didapatkan besar rendemen ekstrak daun cemba sebesar 31,82%. Hasil skrinning fitokimia yang dilakukan, diketahui ekstrak daun cemba mengandung metabolit sekunder berupa alkaloid, flavonoid, tanin, steroid, dan saponin. Hasil uji menunjukkan bahwa ekstrak daun cemba konsentrasi 5% dan kontrol positif dapat menyembuhkan luka pada ± hari ke-10. Kata Kunci: Daun cemba, Povidone iodine, Penyembuhan luka sayat, Skrinning fitokimia